Understanding Domestic Violence in Indonesia Through a Play-with-music: A Story of Wounds - Meilinda Meilinda (k@ta: A Biannual Publication on the Study of Languange and Literature, 2021)
The number of domestic violence is 50% out of violence against woman cases in Indonesia. This condition is intriguing to analyse. There must be a reason behind rising number of crimes related to inequality of women position in the society. One of the ways that can be used to reflect on this subject is through theatre. It is a work of art that can be used to discuss and inspire a necessary social change or social agenda. Therefore, applying textual analysis method on A Story of Wounds, a play by Jessie Monika, I would like to find the reasons behind that inequality to find the core problem of domestic violence as portrayed in ASoW. I utilize Bourdieu’s capital, habitus and field theory to prove that inequality between the wife and the husband, the deeply rooted patriarchy values create imbalance power that open opportunity for domestic violence toward women.